Pengaruh Komposisi Lumpur Ipal Minyak Sawit Dan Cangkang Biji Karet Serta Tekanan Pengepresan Terhadap Nilai Kuat Tekan Briket - Muhammad Fajri Chaniago; Elvi Yenie; Aryo Sasmita (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
WWTP mud (Waste Water Treatment Plant) production of palm oil is the result of sediment from liquid waste containing high organic matter and has not been utilized optimally. WWTP mud produced by palm oil by adding rubber seed shells that can be used as solid fuel in the form of briquettes through a carbonization process with the addition of crude glycerol as an adhesive and can increase the calorific value of the briquettes produced. The adhesive used is crude glycerol because it has high viscosity and density characteristics which can be used as adhesives. In this study the variables used were IPAL sludge ratios for palm oil and rubber seed shell production (90:10, 80:20, 70:30, and 60:40% bb) and pressing pressures (50, 75, and 100 bar) with percentages crude glycerol 40% of the total weight of briquettes. The best compressive strength of 0.1428 kg / cm2 at ratio of 60: 40% with a pressure of 100 bar. The process conditions that have a very significant effect on the compressive strength that significantly influences is ratio of raw materials and pressing pressure which affects the yield. Keywords: Glycerol Crude, Carbonization, Briquette, IPAL Mud (Waste Water Treatment Plant) produced by palm oil, Rubber Seed Shell.